ANALISIS KEBIJAKAN K3 MARITIM DALAM MENUNJANG SISTEM TRANSPORTASI LAUT DI PELABUHAN BELAWAN - Silvia Eliza (CV. Adiba Aisha Amira, 2023)
This study aims to analyze sea transportation policies at Belawan port in realizing modern maritime highway transportation and increasing development. Research using descriptive-qualitative method. The results of the research are as follows: 1) the Government's policy regarding the sea highway is to navigate goods transportation, guarantee the availability of goods, reduce price disparities and ensure the continuity of services for the implementation of goods transportation to underdeveloped, remote, outermost and border areas; 2) the sea transportation development policy is aimed at increasing the role of the national shipping fleet, both domestic and export- import by imposing the cabotage principle; eliminating illegal levies at ports through increased coordination for all agencies related to the process of loading and unloading of goods and meeting international shipping standards and implementing International Ship and Port Security; restructuring shipping laws and regulations and their implementation, as well as institutions in the sea transportation sub-sector in order to create conditions capable of attracting private interest in the development of sea transportation infrastructure; 3) sea transportation policy is determined as the lifeblood of increasing national development for the smooth flow of people, goods, and information. This policy is to support the achievement of an optimal allocation of economic resources, so that sea transportation services are fairly evenly distributed and aflordable to the public's purchasing power.